(3GdHQgGf GdcGTa aj EYLGR GdbQBf GdcQjes - (3ceGd GdOjf CHh GdecGQe YHO GdhGMO Hf YHO GdcQje Hf Nda GdRedcGfis; (3eMeO Hf RjO Hf Ydj Hf GdMSjf GdhGSWj, CHh YHO Gddg,J (B307 (3g` s ((3RcQjG Hf jMji GdHdHjSi s)
(3ChdgG (B:s
(3Hc Gddge GdhGMO GdCRdi GdHGbi GdSQeOi GdaUd GdChd ai MbjbI Yde GdHjGf hGdZQV efg hWQjb JMUjdg s
(3BNQgG (B:s
(3hddg GdbGFd ef Ufa abO GSJgOa aEf CUGH abO GSJYWa aEf CSGA abO GSJbPa hGddg GdeCehd ai JVYja GdKhGH Je s
(3HgG fXGe GdJYbjHIs
(3PcQ Ydi UaMI GdYfhGf Cfg dceGd GdOjf eMeO Hf Ydi GdRedcGfi GdTGaYi J (B727s
(3fbd ef NW GdYdGeI HgGA GdOjf eMeO Hf GHQGgje Hf eMeO GdfMGS GdMdHi s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs